(untitled) (Research, Society and Development, 2025)
Introduction: Pain assessment is closely related to significant outcomes in patients under intensive care; however, its measurement remains challenging, particularly in non-communicative patients such as those who are sedated, intubated, or on mechanical ventilation. It is known that absent or incorrect pain assessment can lead to physiological and psychological complications, increasing morbidity and mortality in Intensive Care Units (ICUs). Furthermore, it is essential to highlight the importance of the Behavioral Pain Scale (BPS) and the Critical-Care Pain Observation Tool (CPOT) as behavioral pain assessment tools for non-communicative and sedated patients in ICUs. Additionally, the emergence of new tools for pain assessment must be noted. Objectives: This integrative review aimed to identify and synthesize qualitative and quantitative evidence regarding pain assessment in patients under intensive care. Methods: A comprehensive search of three electronic databases (Medline, PubMed, and Scopus) was conducted to analyze pain assessment in patients under intensive care. Two authors were involved in selecting studies based on the PRISMA protocol guidelines. Results: From the initial search yield of 2,802 studies, 12 studies were included in the analysis. Conclusion: Regular assessment of pain intensity leads to better outcomes and an improved quality of life for patients in the ICU.